Translating Beowulf: Modern Versions in English Verse. - Hojnowski, Jules Austin (Rocky Mountain Review of Language & Literature (1948-2833))
The article reviews the book "Translating 'Beowulf': Modern Versions in English Verse," by Hugh Magennis.